Recovery of the Aleutian Cackling Goose Branta hutchinsii leucopareia: 10-year review and future prospects - Mini, Anne E; Bachman, Dominic C; Cocke, Josh; Griggs, Kenneth M; Spragens, Kyle A; Black, Jeffrey M (Wildfowl, 2013)
Aleutian Cackling Geese Branta hutchinsii leucopareiawere feared extinct until a remnant population was discovered on Buldir Island by Robert â€œSea Otterâ€ Jones in 1962. Population declines, primarily due to predation by Arctic Foxes Alopex lagopus introduced to the breeding islands, resulted in the listing of Aleutian Cackling Geese as endangered in 1967. Fox removal, translocation of captive birds and captive breeding programmes boosted the remarkable recovery of this sub-species from 790 individuals in 1967 to > 30,000 in 2001, when it was removed from the United Statesâ€™ Endangered Species List. Population estimates currently exceed 100,000 birds. However, the population recovery has brought complex management issues, including the harvest of a once-endangered sub-species and conflict with agricultural interests. This review comes 50 years following rediscovery of the remnant population, 20 years after initial reclassification from endangered to threatened, and 10 years after formal delisting from the United Statesâ€™ Endangered Species Act. This review describes the events leading up to the birdâ€™s recovery, details management actions taken on behalf of the sub-species, and recommends strategies for ensuring that this conservation success story continues into the future.